Brothers and barbarians: Discursive constructions of ‘refugees’ in Russian media - Moen-Larsen, Natalia (Acta sociologica, 2020)
This article maps the unexplored terrain of representations of refugees in Russian media, using discourse theory and the concepts of subject positions and symbolic boundaries to analyse these representations. The research questions are: Who are the refugees? What discourses do they feature in? What kinds of symbolic boundaries do these representations maintain? This study analyses the three Russian newspapers Izvestija, Novaya gazeta and Rossiiskaya gazeta, focusing on how, between 1 January 2014 and 31 December 2015, these newspapers came to employ the term ‘refugee’ for persons from Ukraine and for those from the Middle East and North Africa (MENA). Analysis of the subject position of ‘refugee’ in discourses about security, humanitarianism, integration and nationalism reveals contrasting images of refugees from Ukraine and MENA refugees. The latter are represented as ‘threatening’ and ‘alien’: symbolic boundaries are maintained between Russians and these refugees as well as between ‘superior’ Russia and ‘inferior’ Europe. In contrast, refugees from Ukraine are often presented as similar to Russians. Nationalist discourse merges with security, humanitarian and integration discourses, creating contrasting symbolic boundaries between these two groups of refugees and Russians. Refugees are classed as ‘preferred’ or ‘non-preferred’ migrants on the basis not of their situation, but their ethnicity.